Dehydroepiandrosterone (DHEA) in postmenopausal women - Karasek, Michał (Menopause Review/Przegląd Menopauzalny, 2005)
Dehydroepiandrosterone (DHEA) received recently a great deal of attention, is often advertised as substance delaying aging, and is available in Poland without prescription. Therefore, in the present review basic data on DHEA biosynthesis and metabolism, age-dependent changes in its secretion, significance of DHEA deficiency, and prerequisites for its supplementation are discussed.